Sustainability-Oriented English for Specific Purposes Learning in TVET: A Comparative Study of Green Communication Competence between Indonesia and China - Dian Heriani; Tiur Simanjuntak; Evi Agustinasari; Xinzhi Wang (Journal of Education Technology, 2026)
The growing urgency of sustainability education demands innovative pedagogical approaches that align language learning with ecological responsibility; yet, the integration of sustainability principles into English for Specific Purposes (ESP) remains underexplored, particularly in Technical and Vocational Education and Training (TVET) contexts. This study analyzes, evaluates, and synthesizes strategies for effectively embedding Ecological English Language Teaching (Eco-ELT) into ESP curricula to cultivate Green Communication Competence, defined as the ability to communicate knowledgeably, critically, and ethically about environmental and sustainability issues. Using a mixed-methods design, the research draws on survey and interview data from ESP practitioners to examine pedagogical orientations, institutional support mechanisms, and perceived challenges in implementing Eco-ELT. Findings reveal that while systemic and policy-driven implementation (as seen in one context) ensures coherence and scalability, teacher-led, context-responsive innovation (as in another) fosters adaptability and local relevance, both pathways converging toward the shared aim of sustainability-oriented language education. Ultimately, the study concludes that Eco-ELT serves as a transformative framework for reorienting ESP toward responsible, future-ready communication, empowering learners to engage meaningfully in global sustainability discourses.